Fire protection drawing of BRAC University New Campus Project for RAJUK - BUCG-ABC Joint Venture (BUCG-ABC JV) (BRAC University, 2024)
This record contains mechanical as-built drawings of the Brac University New Campus Project. It consists of DWG versions of drawings.